2000
DOI: 10.1002/1097-4660(200011)75:11<1026::aid-jctb306>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of entrapped catalase using photo-crosslinked resin gel for use in wastewater containing hydrogen peroxide

Abstract: Catalase immobilized using photo-crosslinkable resin was applied to treatment of wastewater containing a low concentration of hydrogen peroxide. The structure of photo-crosslinked resin gel was stable even in the acceleration test of concentrated hydrogen peroxide for a long period. Accordingly, the most important subject of this process was maintaining long term catalase activity. The stabilization of immobilized catalase was investigated by modifying gel carriers with some prepolymers and functional monomers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…This high stability suggests that very little leakage of the immobilized enzymes occurred under repeated washing. The mixing of AOT with a-amylase affected the enzyme activity by forming a protective layer of surfactant around the enzyme (Iida et al, 2000). Similar conclusions were reported by other workers with different enzymes, polymers, and crosslinkers (Yang, et al, 1995;Dessouki and Atia, 2002).…”
Section: Reuse Efficiencysupporting
confidence: 87%
“…This high stability suggests that very little leakage of the immobilized enzymes occurred under repeated washing. The mixing of AOT with a-amylase affected the enzyme activity by forming a protective layer of surfactant around the enzyme (Iida et al, 2000). Similar conclusions were reported by other workers with different enzymes, polymers, and crosslinkers (Yang, et al, 1995;Dessouki and Atia, 2002).…”
Section: Reuse Efficiencysupporting
confidence: 87%
“…At very high enzyme concentrations, on the other hand, irreversible formation of aggregates consisting of thermally denatured enzymes is promoted . Catalase was stabilized by immobilization in solid supports . We reported that the quaternary structure and activity of bovine liver catalase were stabilized by encapsulating in phospholipid vesicles, i.e.…”
Section: Introductionmentioning
confidence: 99%